Residual effects of integrated nutrient management on the performance of cowpea (Vigna unguiculata) in maize-barley-cowpea rotation in northwestern India - Singh, G; Walia, SS; Singh, SP; Bhagat, R; Kaur, S; Sharma, K (Plant Science Today, 2026)
Efficient nitrogen management is vital for realising potential crop productivity. Hence, a two-year field experiment (2023–24 and 2024–25) was conducted at the Punjab Agricultural University, Ludhiana, to evaluate the residual effects of sustainable integrated nitrogen management (INM) practices applied to preceding maize and barley on growth, yield and profitability of the succeeding cowpea. Fourteen INM treatments [T1 [100 % nitrogen (N) from farmyard manure (FYM)], T2 (100 % N from FYM + residue), T3 [75 % N from FYM + 25 % from chemical fertilizer (CF)], T4 (75 % N from FYM + 25 % from CF + residue), T5 (50 % N from FYM + 50 % from CF), T6 (50 % N from FYM + 50 % from CF + residue), T7 (25 % N from FYM + 75 % from CF), T8 (25 % N from FYM + 75 % from CF + residue), T9 (100 % from CF + 25 % N extra from FYM), T10 (100 % from CF + 25 % N extra from FYM + residue), T11 (100 % from CF), T12 (100 % from CF + residue), T13 (Cowpea intercropping in maize without fertilizer + residue retention in barley) and T14 (Control)] were applied to previous crops (maize and barley). The results showed that being statistically at par with the treatments (T1, T2, T3, T4 and T5), the treatment T6 recorded significantly higher growth parameters [plant height (95.1 and 95.8 cm), LAI (3.51 and 3.52) and dry matter accumulation (38.2 and 39.0 g/plant)] and yield attributes [pods/plant (21.3 and 22.4), pod length (20.1 and 20.7 cm) and seeds/pod (11.8 and 12.0)] of cowpea over other treatments, consequently resulting in higher productivity (54.56 and 55.76 % more green pod yield over control) and economic benefits.